EFSUMB Guidelines 2011: Comments and Illustrations - Dietrich, C. F.; Cui, X. W.; Schreiber-Dietrich, D. G.; Ignee, A. (Ultraschall in der Medizin - European Journal of Ultrasound, 2012)
The European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB) introduced the first guidelines on the use of contrast-enhanced ultrasound (CEUS) in 2004. This EFSUMB document focused mainly on liver applications. However, new applications extending beyond the liver were subsequently developed. Therefore, in the update of the clinical recommendations on the use of CEUS by the EFSUMB, applications in other organs were also described and published in 2008. Increased interest in recent years in the CEUS technique and in the application of CEUS in novel fields has resulted in CEUS indications and applications for nearly all organ systems. As a result, the EFSUMB initiated a new update of the guidelines in 2011 to include this additional knowledge. Some of the indications are established, whereas others are preliminary. The latter indications are categorized as emergent CEUS applications since the available evidence is insufficient for general recommendation. This article focuses on comments, illustrations and examples of the application of CEUS in the pancreas, spleen, gastrointestinal tract, kidney, adrenals, lymph nodes, perineum, and hepatobiliary system. The potential for endoscopic ultrasound to highlight the importance of CEUS in the daily routine is also addressed.
Keywords: diagnosis; characterisation; metastases; hepatocellular carcinoma; guidelines; hemangioma; microbubble contrast agent